Novel Approaches for Treating Autonomously Functioning Thyroid Nodules - Pace-Asciak, Pia; Russell, Jon O.; Shaear, Mohammad; Tufano, Ralph P. (Frontiers in Endocrinology, 2020)
Benign thyroid nodules are exceedingly common in the adult population. Only a small percentage of nodules are toxic or autonomously functioning thyroid nodules (AFTN). The options clinicians have for treating the symptoms of hyperthyroidism include anti-thyroidal medications, radioactive iodine or surgery. Depending on the patient population treated, these options may not be suitable or have inherent risks that are undesirable to the patient. On the other hand, untreated hyperthyroidism can lead to osteoporosis, atrial fibrillation, emotional lability and neurological consequences. Thus, we present a review of two novel safe and effective approaches for treating AFTN; one surgical (transoral endoscopic thyroid surgery) and one nonsurgical (radiofrequency ablation), as a means for expanding our treatment armamentarium.